2017
DOI: 10.1128/aem.00592-17
|View full text |Cite
|
Sign up to set email alerts
|

Improved α-Amylase Production by Dephosphorylation Mutation of CreD, an Arrestin-Like Protein Required for Glucose-Induced Endocytosis of Maltose Permease and Carbon Catabolite Derepression in Aspergillusoryzae

Abstract: Aspergillus oryzae produces copious amount of amylolytic enzymes, and MalP, a major maltose permease, is required for the expression of amylase-encoding genes. The expression of these genes is strongly repressed by carbon catabolite repression (CCR) in the presence of glucose. MalP is transported from the plasma membrane to the vacuole by endocytosis, which requires the homolog of E6-AP carboxyl terminus ubiquitin ligase HulA, an ortholog of yeast Rsp5. In yeast, arrestin-like proteins mediate endocytosis as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Because the A. nidulans stain used to express CreA‐GFP contained the creB allele ( creB15 ), which had a mutation comprising a single amino acid substitution, we hypothesize that this mutation is not sufficient to abrogate the reduction in the level of CreA protein. The reduced CreA abundance in the creB disruption mutant was consistent with our recent study that showed the transcriptional relief of α‐amylase gene expression from CCR by A. oryzae creB disruption (Tanaka et al, ). However, a recent report suggests that CreA is not a direct target for CreB, although interaction between CreA and CreB was observed when they were overexpressed (Alam et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Because the A. nidulans stain used to express CreA‐GFP contained the creB allele ( creB15 ), which had a mutation comprising a single amino acid substitution, we hypothesize that this mutation is not sufficient to abrogate the reduction in the level of CreA protein. The reduced CreA abundance in the creB disruption mutant was consistent with our recent study that showed the transcriptional relief of α‐amylase gene expression from CCR by A. oryzae creB disruption (Tanaka et al, ). However, a recent report suggests that CreA is not a direct target for CreB, although interaction between CreA and CreB was observed when they were overexpressed (Alam et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…It is thought that CreA is degraded via ubiquitination by HulA and CreD, and stabilized through deubiquitination by the CreB/CreC complex (Lockington and Kelly, ; Boase and Kelly, ). Previously, we reported that A. oryzae CreD is required for carbon catabolite de‐repression (Tanaka et al, ). When FLAG‐CreA was expressed from its own promoter in the Δ creD strain, the abundance of FLAG‐CreA was comparable with that in the wild‐type strain, even after incubation in 1% maltose medium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations